Autonomic nervous system maturation in preterm neonates: Correlation with gestational and postmenstrual age (ProMote) - Theano Kokkinaki; Aristeidis Petrakis; Ιoannis Kyprakis; Νicole Anagnostatou; Μaria Markodimitraki; Theano Roumeliotaki; Μanolis Tzatzarakis; Έlena Vakonaki; Αristidis Tsatsakis; Haridimos Kondylakis; Εleftheria Hatzidaki (PLoS ONE, 2026)
Background Autonomic nervous system (ANS) maturation is crucial for neonatal adaptation, but in preterm infants, this process is often delayed, leading to increased vulnerability. Heart rate variability (HRV) provides a non-invasive measure of ANS function, yet existing evidence is contradictory regarding how birth gestational age influences HRV development at comparable postmenstrual ages. Objective This study aims to investigate HRV metrics at 35–36 weeks postmenstrual age in preterm neonates with a wide range of birth gestational ages. We hypothesize that lower birth gestational age correlates with reduced HRV, indicating delayed ANS maturation and diminished parasympathetic tone. Methods We conducted a longitudinal cohort study of preterm neonates divided into two groups: Group A (28–33 weeks GA) and Group B (34–36 weeks GA). Short-term HRV recordings (mean duration 17 minutes, SD 4.3) were obtained within 24 hours after birth, on the 3rd–4th postnatal day, and again at 35–36 weeks PMA for neonates born before 35 weeks. HRV features included time-domain, frequency-domain, and non-linear measures. Results Of 132 recruited preterm neonates, 88 were included in the final analysis. Preterm neonates with higher gestational age at birth (Group B) exhibited elevated time-domain measures (HTI, SDNN, RMSSD, pNN50) and higher frequency-domain indices (LF, LF/HF, TP) compared with those born earlier (Group A). Compared with Group B, Group A (28–33 weeks GA) had higher mean heart rates and exhibited stronger long-range correlations in heart rate dynamics. Conclusion This study demonstrates that advancing gestational age is associated with greater parasympathetic modulation and more balanced sympathovagal control. Birth gestational age is a strong determinant of autonomic nervous system development at 35–36 weeks postmenstrual age. These findings highlight the importance of stratifying by gestational age in HRV studies and may inform neurodevelopmental monitoring and NICU care strategies.